IC 9431 Laboratory Procedures For Hydrometallurgical-Processing And Waste-Management Experiments - D. C. Seidel (The National Institute for Occupational Safety and Health (NIOSH), 1995)
This report describes generic procedures and equipment arrangements for conducting laboratory-scale hydrometallurgical and related waste-management experiments. It provides a starting point for personnel who have received or are receiving professional training, but do not have specific experience in laboratory procedures. With guidance, it also has application as a resource for technician training. The publication contains chapters on laboratory safety, feed-sample preparation, leaching, solids-liquid separation, and recovery from solution.